Stress distribution in an infinite elastic body with a locally curved fiber in a geometrically nonlinear statement - Akbarov, S. D.; Kosker, R.; Simsek, K. (SPRINGER, 2005)
Within the framework of a piecewise homogeneous body model, with the use of three-dimensional geometrically nonlinear exact equations of elasticity theory, a method for determining the stress-strain state in unidirectional fibrous composites with locally curved fibers is developed for the case where the interaction between the fibers is neglected. All the investigations are carried out for an infinite elastic body containing a single locally curved fiber. Numerical results illustrating the effect of geometrical nonlinearity on the distribution of the self-balanced normal and shear stresses acting on the interface and arising its a result of local curving of the fiber are presented.
Keywords: fibrous composites; local curving; geometrical nonlinearity; stress distribution; COMPOSITES; MODEL; Mechanics; Materials Science; Polymer Science